Effectiveness of house dust mite acaricide tri-n-butyl tin maleate on carpets, fabrics and mattress foam: a standardization of methodology - Uehara, Satiko; Franzolin, Marcia Regina; Chiesa, Soledad; Moreira, Débora; Gambale, Walderez; Paula, Claudete Rodrigues (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
The aim of this study was to determine the effectiveness of the acaricide tri-n-butyl tin maleate, industrially applied to samples of carpets, mattress foam, and fabrics used for furniture upholstery, soft toys and shoe uppers. Approximately 100 adult house dust mites of the species Dermatophagoides pteronyssinus were inoculated into a Petri dish containing the sample (a piece of carpet, mattress foam, or fabric), treated with the acaricide, randomly collected. Mite-maintenance culture medium was added on top of each sample. After one, two, three, seven and 30 days of incubation at 25 ºC and 75% relative humidity, each dish was examined using a 40X stereoscopic microscope (40X). One hundred percent acaricide effectiveness was obtained in treated materials by the end of the 30th-day postinoculation period, under optimal conditions for mite maintenance.